Організація супутніх послуг аудитора в сучасних умовах господарювання - Бурова, Т.А. (Культура народов Причерноморья, 2013)
У статті розглядаються питання організації супутніх послуг в Україні, в основному оцінки концептуальних напрямів функціонування підприємств у зовнішньому середовищі, стану системи внутрішнього управління, облікової та податкової політики підприємства. Оцінка стратегії діяльності підприємства передбачає аудит статутної діяльності, аналіз чистих активів підприємства, організації маркетингу, конкурентоспроможності продукції та її оновлення, аналізу фінансової політики та перспектив економічного розвитку підприємства. В статье рассматриваются вопросы организации сопутствующих услуг аудитора в Украине, в основном оценки концептуальных направлений функционирования предприятий во внешней среде, состояния системы внутреннего управления, учетной и налоговой политики предприятия. Оценка стратегии деятельности предприятия предусматривает аудит уставной деятельности, анализ чистых активов предприятия, организации маркетинга, конкурентоспособности продукции и ее обновления, анализа финансовой политики и перспектив экономического развития предприятия. The article deals with the organization of related services in Ukraine, mainly evaluation of conceptual directions functioning of the external environment of the system of internal control, accounting and tax policies of the enterprise. Providing different types of services require auditors' professional competence and high professional level in the field of accounting and its subsystems, financial and tax accounting, business law, modern taxation, financial and economic analysis and other issues. The aim of the paper is the description of certain audit related services, such as evaluation of conceptual functioning referral business in today's economy. The use of legal and regulatory framework of accounting, taxation, law requires the auditor, especially evaluating the general characteristics that define the position and strategic direction of the company in the domestic and external environment and make the concept of its operation. Audit Strategy functioning of the external environment involves studying the following issues: statutory activities, analysis of net assets of the company and the share capital, organization of marketing competitiveness and updating, analysis of financial policy of the company, the prospects for economic development.